The Association between Maternal Race and Ethnicity and Risk Factors for Primary Cesarean Delivery in Nulliparous Women - Stark, Elisabeth L.; Grobman, William A.; Miller, Emily S. (American Journal of Perinatology, 2019)
Objective To understand whether maternal, perinatal, and systems-level factors can be identified to explain racial/ethnic disparities in cesarean delivery rates.Study Design This retrospective cohort study included nulliparous women with singleton gestations who delivered at a tertiary care center from 2015 to 2017. Maternal, perinatal, and systems-level factors were compared by race/ethnicity. Multilevel multivariable logistic regression was used to identify whether race/ethnicity was independently associated with cesarean. Effect modification was evaluated using interaction terms. Bivariable analyses and multinomial logistic regression were used to determine differences in indication for cesarean.Results Of 9,865 eligible women, 2,126 (21.5%) delivered via cesarean. The frequency of cesarean was lowest in non-Hispanic white women (19.2%) and highest in non-Hispanic black women (28.2%; p < 0.001). Accounting for factors associated with cesarean delivery did not lessen the odds of cesarean associated with non-Hispanic black race (aOR: 1.58, 95% CI: 1.31–1.91). Compared with non-Hispanic white women, non-Hispanic black women were more likely to undergo cesarean for nonreassuring fetal status (aOR: 2.73, 95% CI: 2.06–3.61).Conclusion Examined maternal, perinatal, and systems-level risk factors for cesarean delivery did not explain the racial/ethnic disparities observed in cesarean delivery rates. Increased cesarean delivery for nonreassuring fetal status contributed substantially to this disparity.
Keywords: cesarean delivery; racial disparity; nonreassuring fetal status; night float